Agricultural producer perceptions of climate change and climate education needs for the Central Great Plains - Campbell Hibbs, Amber; Kahl, Daniel W.; PytlikZillig, Lisa; Champion, Ben; Abdel-Monem, Tarik; Steffensmeier, Timothy R.; Rice, Charles W.; Hubbard, Kenneth (My University, 2014)
The Central Great Plains Climate Education Partnership conducted focus groups throughout Kansas to gain a better understanding of farmer perceptions and attitudes towards climate change education. Results indicate concern about climatic changes, even if producers are unsure that "human caused climate change" is occurring. Participants indicated they would like access to information through Web-based programs that allow them to manipulate variables relevant to their area and situation. Participants prefer locally relevant information and identified Extension agents as trusted educators. The study provided an expanded understanding of agricultural producer perceptions that will be valuable to individuals or organizations providing climate education.
Citation: Hibbs, Amber Campbell, Daniel Kahl, Lisa PytlikZillig, Ben Champion, Tarik Abdel-Monem, Timothy Steffensmeier, Charles W. Rice, and Kenneth Hubbard. “Agricultural Producer Perceptions of Climate Change and Climate Education Needs for the Central Great Plains.” Journal of Extension 52, no. 3 (June 2014). https://www.joe.org/joe/2014june/a2.php.
Keywords: Climate change education; Climate change adaptation; Agricultural perceptions; Education